Linguicide and the Realm of New Zealand - Nicholas, Sally Akevai D; Koka‘Ua, Jesse (Waka Kuaka, 2025)
“New Zealand proper” is home to the majority of the population of the so-called Realm of New Zealand countries along with significant populations from the independent nations of Sāmoa and Tonga. All these groups are facing language maintenance challenges, similar to so many Indigenous language groups in the world today. However, there is stark contrast in the maintenance status between the languages of the Realm and those of the independent nations. Bluntly, the Realm languages are severely endangered in comparison with Samoan and Tongan. This paper describes how the Realm of New Zealand has enacted and continues to enact linguicide on the languages of the Realm while at the same time deliberately invisibilising the existence of the Realm. It proposes that Indigenous peoples of the Realm should reorient their language revitalisation focus away from the “home” and the individual to the level of the community, and pursue trans-Indigenous collaboration with tangata whenua (the Māori people of Aotearoa or New Zealand proper) along with other tangata moana (Indigenous peoples of the Pacific) who are manuhiri (guests) in Aotearoa.